Autoimmune polyendocrine syndrome and thrombocytosis. Issue 6 (2nd November 2015) - Atquet, V.; Lienart, F.; Vaes, M.
Abstract : We describe a woman aged 37 years, affected with Hashimoto's thyroiditis, detected since the age of 17, with gonadic insufficiency with anti-ovarian antibodies since the age of 22 years and Addison's disease since 24 years old. At that moment, the diagnosis of autoimmune polyendocrine syndrome (APS) was made. Concomitant to this diagnosis, thrombocytosis was detected and aetiological assessment revealed an atrophy of the spleen. Differential diagnoses of APS and hyposplenism will be discussed. We will look at a possible association between these two pathologies. Indeed, asplenism is found in approximately 20% of adults affected by type 1 APS, also called auto-immune polyendocrinopathy candidiasis ectodermal dystrophy (APECED) syndrome. The most likely aetiology for this atrophy of the spleen is a destruction of auto-immunological origin. However, in our patient, the search for a mutation of the autoimmune regulator (AIRE) gene proved negative. This mutation is commonly, but not systematically, present in type 1 APS. A type 2 APS should then be considered.